Testing Antibacterial Activities and Characterization of Chemical Compounds Composing Essential Oil from Lemo Cuco Fruit Peel (Citrus sp.) - Febryanti, Amalyah; Ilyas, Asriani; Abubakar, Andi Nur Fitriani (Brawijaya University, 2024)
Lemo Cuco (Citrus sp.) is one of the plant species of Rutaceae grown in the districts of Bone and Sinjai, South Sulawesi. This fruit is commonly used for food as scent, cough reliever and as fishy and meaty deodorizing. The peel has a special scent indicating presence of essensial oil components. This study aims to evaluate antibacterial activities and and to characterize compounds in ethanol extract dan n-hexane extract Lemo Cuco (Citrus sp.). This study used the soxhletation, and fitokimia text and the characterization of components in extracts with GC-MS and antibacterial activities using the disc diffusion method. The results obtained from the study were testing the antibacterial activities of Lemo Cuco (Citrus sp.) peel extract against the Staphylococcus aureus and Salmonella typhi bacteria. Inhibition of ethanol and n-hexane extract against the bacteria S. aureus included weak, medium, and strong category according to the concentrations (20%, 10%, 5%, 2.5% and 1.25%), whereas inhibitory against S. typhi bacteria in n-heksane included weak, medium, and strong category, whereas ethanol extract included medium and weak category, even not active. Based on the results of phytochemical identification of the Lemo Cuco (Citrus sp.), peel extract indicated existence of flavonoids, phenolic, steroids, terpenoids, alkaloids and saponins compound. n-heksane exctract contained special fraction saponins, whereas ethanol exctract was nothing. Characterization using GC-MS indicated existence of monoterpenoid and sesquiterpenoid compound. Thus, ethanol and n-hexane extracts of lemon cuco fruit skin have the potential to inhibit Staphylococcus aureus bacteria.